Estudo retrospectivo clínico-radiográfico de implantes curtos em região posterior - Segalla, Douglas Blum (2020)
Edentulous posterior regions in maxilla and mandible often have limited bone quantity, and short implants are a clinical alternative for prosthetic rehabilitation. This study aimed to retrospectively evaluate (approximately 10 years) short implants restored with prosthetic crowns in the posterior region of the maxilla and mandible, to assess implant survival and prosthesis success rates, as well as identifying possible risk factors for failure. The sample consisted of 85 implants and 83 prostheses installed in 30 patients, who received both 6mm and 8mm implants in the same arch. Data were collected by using clinical and radiographic exam, standardized questionnaires, maximum bite force measurement, and clinical crown/implant ratio measurement. Data were analyzed by descriptive and inferential statistics with univariate and hierarchical multivariate models at a significance level of 0.05. Two implants were lost, both before prosthesis installation, and 10 cases of prosthetic failure (loss of screw tightening) occurred in five patients, with a success rate of 87.9%. The logistic regression models used to estimate the odds ratio for prosthesis failure showed that only the variable clinical crown/implant ratio had a significant effect (P<0.05). Within the study limitations, the results suggest that both 6mm and 8mm implants placed in the posterior region do not differ in implant survival and prosthesis failure in 10 years of clinical function. Among the tested variables, only the increase in clinical crown/implant ratio had an effect on an increase in prosthesis failure. However, all cases of loss of screw tightening were easily solved clinically and do not characterize a definite failure with prosthesis loss.